Rootstock Susceptibility to «Phaeomoniella chlamydospora» and «Phaeoacremonium» spp. - Khan, Adalat; Eskalen, Akif; Gubler, W. Douglas (Phytopathologia Mediterranea, 2001)
Twenty healthy cuttings each were inoculated artificially with Phaeomoniella chlamydospora, Phaeoacremonium inflatipes and Phaeoacremonium aleophilum. After the formation of callus, they were planted in pots. Approximately one year after inoculation, disease occurrence was recorded as the length of brown vascular streaking from the base of plant toward the shoot tip. Discolored areas were cultured on potato dextrose agar amended with tetracycline hydrochloride (PDA-tet) and pathogens were re-isolated. Inoculation with Pa. chlamydospora showed that rootstocks 3309, 420A, 110R, 5C, Schwarzmann, St. George, and Salt Creek were least susceptible, while 99R, 39-16, Freedom, Riparia Gloire, 140Ru, 16-16 and 1103 were most susceptible. When inoculated with Pm. inflatipes, 16-16, 3309, AXR1, Salt Creek, 110R, 5C, Freedom and 140Ru were least susceptible, while 420A, St. George, 161-49, and Harmony were most susceptible. Inoculation with Pm. aleophilum showed that 1103, 420A, Harmony, and Salt Creek were least susceptible, while 110R, SO4, 39-16 and 161-49 were most susceptible. The susceptibility of the rootstocks and the occurrence of vine decline in the field in California did not appear to be well correlated because 3309, 101-14, 5C, and 110R were always most susceptible. But these rootstocks are the most widely planted, and hence the natural occurrence of the disease is probably skewed towards these rootstocks. However, since no resistance was detected in our study, even though there was a wide range of susceptibility, the degree of rootstock susceptibility may not be such an important factor in disease expression under natural conditions.